Factors Causing Delay to Surgical Treatment in Geriatric Neck of Femur Fracture Patients: A Case Control Study - Hamza Chaudhary, Ariba Waheed (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Neck of femur fracture is a common orthopaedic condition that is treated operatively; the annual incidence rate is estimated to be 6.26 million by 2050. Objectives: To know and work on actual facts causing delay in treatment and work on them. Materials and Methods: This was a retrospective review of patient records at a General Hospital in Dudley West Midlands, UK. Patients undergoing Surgical treatment for intra-capsular (IC) or extra-capsular (EC) hip fractures were included. Sample size is 300. The chi-square test is applied to show the association between the factors involved. The case group includes patients with a surgery time of more than 36 hours, and the control group is the one patients with a less than 36 hours of surgery time. The p-value less than 0.05 is considered to be significant. The permission for the data for this case-control study was taken from the hospital and no IRB approval is required and no data collection tool or technique was needed. The population consists of people suffering from the Neck of femur fracture. Results: A Significant association exists between time to surgery (TTS) and length of hospital stay, with a p-value of 0.036. No significant association exists between TTS and Mortality, with a p-value of 0.924. Among the factors causing delay for the surgery, only gender has been significantly associated with TTS, with a p-value of 0.001. Conclusion: TTS greater than 36 hours significantly affects the duration of hospital stay for more than 2 weeks but has no significant association with the overall Mortality. So when comparing it with the guidelines, if the surgery gets delayed by more than 36 hours, it won’t have a significant impact on the mortality, and other factors might be considered and pre-operative cardiovascular risk assessment and haemoglobin level assessment can be done, ensuring a better outcome for the patient. Key Words: Hip fracture, Mortality.